DIAGNOSIS AND PROPOSAL FOR IMPLEMENTING ENVIRONMENTAL AND SOCIAL PRACTICES IN THE CHEMISTRY AND BIOLOGY TEACHING LABORATORIES OF IFFAR CAMPUS SANTA ROSA - Schneider, Adriana Laiane; Dejavitte, Gabriela Giusmin; Becker, Milena Busnello; Costa, Carla Cristina; Ferrarini, Fabrício (Seven Editora, 2026)
The proper management of chemical and biological waste in higher education institutions is fundamental to minimizing environmental impacts and promoting sustainable practices. In this context, the present study aimed to identify, manage, and minimize the waste generated in the Chemistry and Biology teaching laboratories of the Farroupilha Federal Institute, using the Biological Sciences Degree Course as a pilot study. The research has an exploratory character, with a qualitative and quantitative approach, based on the collection of data regarding the waste produced during practical classes in the second semester of 2024. The results showed that the greatest generation of waste occurred in the activities of the Chemistry for Biological Sciences discipline, especially acid-base solutions and chemical waste containing solvents and laboratory reagents. Organic waste from Botany, Plant Physiology, and Microbiology practices was also identified. The study highlighted the importance of segregation, neutralization, and proper storage of waste, as well as the need to improve quantitative and qualitative control through standardized monitoring spreadsheets. The integration of Environmental, Social and Governance (ESG) principles and the Sustainable Development Goals (SDGs) contributed to strengthening more responsible and sustainable laboratory practices, promoting environmental awareness among undergraduate students. It is concluded that the implementation of waste minimization and management strategies in the academic environment favors the training of professionals more committed to sustainability and allows for the replication of these practices in other courses and campuses of the institution.